Applications of Fibre Reinforced Concrete - M. Muthukanna, Ance Mathew (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
One of the commonly used building materials is concrete since it has many advantages. But due to its low tensile strength, it cannot be used alone everywhere. Therefore, steel is widely used to reinforce concrete. But due to its high cost, bamboo is one of the ways to replace reinforcement bar in concrete for low-cost construction. Due to its renewable nature and eco-friendly benefit, it plays a vital effort to prevent air pollution because it absorbs nitrogen. Bamboo grows in a few years and reaches its maximum strength and it is a natural fiber that helps to improve the strength of concrete and thereby used to reinforce concrete materials. In this research work, fiber-reinforced concrete is produced using bamboo as a reinforcing block material. Tests are done with C-25 grade concrete and the compressive strength, tensile strength, and flexibility of bamboo fibers are tested and compared with plain concrete